Some Notes on Economic Growth in Argentina and Brazil during 2003-2015 - Lazzarini, Andrés Lucas Rodrigo (2017)
The paper analyses some factors that explain the positive trend in economic growth for Brazil and Argentina in 2003-2015, such as the improvement in the external conditions as well as the economic policies oriented to boost domestic aggregate demand. On the other hand, these economies have, in recent years, undergone a marked slowdown. The key factor to understand the drop in economic activity in Argentina has been the worsening of the external constraint since 2012; while for the Brazilian case the main causes have to be sought in a deliberate shift in the orientation of its economic policy since 2011.